Analysis by Mass Spectrometry of the Polar Lipids from the Cellular Membrane of Thermophilic Lactic Acid Bacteria - Fernandez Murga, María Leonor (2000)
Fast atom bombardment (FAB) technique was employed to determine the structure of polar lipids from the cellular membrane of Lactobacillus delbruekii ssp. bulgaricus and Streptococcus salivarius ssp. thermophilus. Analysis of spectra provided useful information about the molecular species and aminoacids constituents of the samples.